Enhanced cardiac CaMKII oxidation and CaMKII-dependent SR Ca leak in patients with sleep-disordered breathing - Arzt, Michael; Drzymalski, Marzena A.; Ripfel, Sarah; Meindl, Sebastian; Biedermann, Alexander; Durczok, Melanie; Keller, Karoline; Mustroph, Julian; Katz, Sylvia; Tafelmeier, Maria; Lebek, Simon; Flörchinger, Bernhard; et al. (Antioxidants, 2022)
Background: Sleep-disordered breathing (SDB) is associated with increased oxidant generation. Oxidized Ca/calmodulin kinase II (CaMKII) can contribute to atrial arrhythmias by the stimulation of sarcoplasmic reticulum Ca release events, i.e., Ca sparks. Methods: We prospectively enrolled 39 patients undergoing cardiac surgery to screen for SDB and collected right atrial appendage biopsies. Results: SDB was diagnosed in 14 patients (36%). SDB patients had significantly increased levels of oxidized and activated CaMKII (assessed by Western blotting/specific pulldown). Moreover, SDB patients showed a significant increase in Ca spark frequency (CaSpF measured by confocal microscopy) compared with control subjects. CaSpF was 3.58 ± 0.75 (SDB) vs. 2.49 ± 0.84 (no SDB) 1/100 µm−1s−1 (p < 0.05). In linear multivariable regression models, SDB severity was independently associated with increased CaSpF (B [95%CI]: 0.05 [0.03; 0.07], p < 0.001) after adjusting for important comorbidities. Interestingly, 30 min exposure to the CaMKII inhibitor autocamtide-2 related autoinhibitory peptide normalized the increased CaSpF and eliminated the association between SDB and CaSpF (B [95%CI]: 0.01 [−0.1; 0.03], p = 0.387). Conclusions: Patients with SDB have increased CaMKII oxidation/activation and increased CaMKII-dependent CaSpF in the atrial myocardium, independent of major clinical confounders, which may be a novel target for treatment of atrial arrhythmias in SDB.
This article belongs to the Special Issue Oxidative Stress in Cardiovascular Diseases
Gesehen am 28.04.2022